Zastosowanie metody wskaźników sezonowości w prognozowaniu dla danych dekadowych - Cheba, Katarzyna (The Application of the Index Seasons Method in Forecasting Decade Data, 2006)
The main objective of this paper was to examine the effectiveness of the inter- and extrapolating methods in forecasting real processes under the condition of missing information, as well as to find out the factors determining their effectiveness. The studies were based on a'vista deposits collected from two banks. The literature presents a variety of numeric methods used for estimating interpolating forecasts. This work suggests how extrapolating forecasts can be applied. The following methods were discussed: a segment method, an arc method I, II, Lagrange method, Chebyshev polynomials. Brown and Holt models and trigonometric polynomial model. The results of empirical studies indicate that econometric methods may be applied to forecast missing data.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 49-58